# Limits

#### raven2k7

need these 2 solved

lim
x-->1 (-x^3 - x^2 - x - 1)=

lim (-3x^2 + 4x - 2)=
x-->00(infinity)

#### JeffM1

need these 2 solved

lim
x-->1 (-x^3 - x^2 - x - 1)=

lim (-3x^2 + 4x - 2)=
x-->00(infinity)
So what have you tried to do so far?

Have you applied the laws of limits as I suggested in a prior post?

#### raven2k7

Yes, I have, but these two still have me a bit confused.

Last edited by a moderator:

#### [email protected]

Yes, I have, but these two still have me a bit confused.
What did you get after applying the law of limits? Can you explain why you are confused?

Last edited by a moderator:

#### raven2k7

The -x and the -3 confuses me.

Last edited by a moderator:

#### [email protected]

Can you tell us what you tried?

Last edited by a moderator:

#### skipjack

Forum Staff
-x^3 is equivalent to -(xÂ³), etc.

If $p(x)$ is a non-constant polynomial in $x$, $$\displaystyle \lim_{x\to\infty}p(x)$$ doesn't exist (strictly speaking), and $$\displaystyle \lim_{x\to k}p(x) = p(k)$$.

Similar Math Discussions Math Forum Date
Calculus
Calculus
Real Analysis
Algebra